High-entropy calcium bismuth niobate-based high-temperature lead-free piezoelectric ceramic and preparation method thereof
By adjusting the structure and reducing the sintering temperature by adjusting the structure of the high-entropy bismuth niobate-based material system, the low-voltage electrical coefficient and Bi element volatility of existing high-temperature piezoelectric materials in high-temperature environments is solved, and ceramic materials with high-voltage electrical coefficient and high Curie temperature are realized, which are suitable for large-scale production.
Patent Information
- Application Number
- CN202411857037.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing high-temperature piezoelectric materials exhibit low-voltage electrical coefficient d33 and volatile Bi elements in high-temperature environments lead to composition deviations, limiting their practical application in the field of high-temperature.
The high-entropy bismuth niobate-based material system is adopted to adjust the structure of the perovskite-like layer, combine it with a sintering agent to reduce the sintering temperature and reduce the volatility of Bi elements, thereby improving the piezoelectric properties and Curie temperature of the ceramic.
The high voltage electrical coefficient d33 is greater than 20pC/N and the high Curie temperature is greater than 900℃, while reducing the volatility of Bi elements and increasing the resistivity of ceramics, which is suitable for large-scale production.
Smart Images

Figure CN119874357A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of high-temperature piezoelectric ceramic materials, and specifically relates to a high-entropy bismuth calcium niobate-based high-temperature lead-free piezoelectric ceramic and a preparation method thereof. Background Art
[0002] Piezoelectric ceramic materials are electronic functional materials that can realize the mutual conversion of electrical energy and mechanical energy. Various piezoelectric components such as vibration sensors and ultrasonic transducers built with piezoelectric ceramic materials as core components are widely used in many civil and military fields such as home appliances, aerospace, medical equipment, and oil exploration. With the rapid development of modern industry and the continuous changes in practical application needs, the application of piezoelectric materials has shifted from conventional use to service in extreme environments such as high temperature, and the industry's demand for high-temperature piezoelectric materials is becoming more and more urgent. Usually, due to the thermal depolarization of piezoelectric materials, their safe use temperature is above their Curie temperature T. C 1 / 2-2 / 3 of the total, which requires its T C At least more than 400℃, and the high-temperature piezoelectric ceramic materials used in high-temperature piezoelectric vibration sensors used in aircraft engines have a higher operating temperature. Some devices use temperatures of ~480℃, and some require ultra-high temperature piezoelectric vibration sensors above 650℃. Regardless of environmental and health requirements or actual operating temperature restrictions, the most widely used commercial lead zirconate titanate-based piezoelectric material (T C ~250-380℃) has irreconcilable defects, which limits its further promotion in the application of high-temperature piezoelectric devices. In addition, the need for sustainable and green development has made people pay more attention to the development of lead-free piezoelectric materials.
[0003] Compared with traditional piezoelectric materials, bismuth layered oxide CaBi 2 Nb 2 O 9 The structure is composed of bismuth oxide layers (Bi 2 O 2 ) 2+ and two perovskite-like layers (CaNb 2 O 7 ) 2- They are arranged alternately along the c-axis direction, have a high Curie temperature (~940℃), good temperature stability, low dielectric loss, excellent insulation, low aging rate, easy sintering, etc. These characteristics make them have great potential in the field of high-temperature piezoelectricity. However, its unique layered structure leads to its piezoelectric coefficient d 33 Low (~5.8pC / N). Moreover, during the high temperature sintering process, the volatilization of Bi element will lead to CaBi 2 Nb 2 O 9The composition deviates from the stoichiometric ratio and even produces a second phase, further reducing its piezoelectric activity. These problems restrict its practical application in high-temperature fields. Improving its piezoelectric properties has become an urgent problem to be solved before large-scale application.
[0004] Although CaBi 2 Nb 2 O 9 There are some shortcomings and problems, but people have improved its piezoelectric activity and expanded its potential in high-temperature piezoelectric applications through strategies such as element doping and process optimization. Among them, the poor piezoelectricity of CaBi has been improved through texture engineering, chemical doping and special sintering technology. 2 Nb 2 O 9 The piezoelectricity of the base ceramics, but under the condition that the Curie temperature is greater than 900℃, the piezoelectric coefficient d 33 It is difficult to reach or even exceed 20pC / N, which cannot meet the requirements of high voltage electrical performance and high Curie temperature. At the same time, the special process is not only costly and complicated, but also unsuitable for large-scale industrial production. Summary of the invention
[0005] To solve the above problems, the present invention provides a high-entropy calcium bismuth niobate-based high-temperature lead-free piezoelectric ceramic and a preparation method thereof. The ceramic composition of the system is a single orthorhombic ferroelectric phase, and has excellent piezoelectric properties, electrical insulation and a high Curie temperature.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] The present invention provides a high-entropy calcium bismuth niobate-based high-temperature lead-free piezoelectric ceramic, the chemical composition of which is Ca 1-x-y (Na 0.5 Bi 0.5 ) x Bi 2+y Ti y Nb 2-y-z Ta z O 9 +u wt%MO,0.1≤x≤0.9,0.1≤y≤0.9,0≤z≤5 / 3,0<u≤0.4, the MO is selected from B 2 O 3 , Fe 2 O 3 , CuO, MnO 2 One or more combinations of .
[0008] Further, the chemical composition is: Ca 1 / 3 Na 1 / 6 Bi 5 / 2 Ti 1 / 3 Nb 5 / 3-z Taz O 9 +u wt%MO,0≤z≤5 / 3, the MO is selected from B 2 O 3 , Fe 2 O 3 , CuO, MnO 2 One or more combinations of .
[0009] The present invention provides a method for preparing the above-mentioned high-entropy calcium bismuth niobate-based high-temperature lead-free piezoelectric ceramic, comprising the following steps: S1. weighing raw materials of metal carbonate or oxide according to a stoichiometric ratio, mixing and calcining once to obtain a pre-synthesized powder; S2. adding a sintering aid to the pre-synthesized powder according to a stoichiometric ratio, performing high-energy ball milling, mixing and granulating, sieving, pressing and sintering to obtain a ceramic sample; S3. polishing the ceramic sample, cleaning and drying it, coating the two end surfaces with silver paste, and polarizing it.
[0010] Furthermore, in the step S1, the mixture is: the metal carbonate or oxide is ball-milled for 8-12 hours with alcohol or water as the medium at a rotation speed of 300-500 r / min, and then dried after the ball-milling.
[0011] Furthermore, the process parameters of the primary calcination are: calcining the dried mixed raw materials in an air environment, with a synthesis temperature of 800-900° C. and keeping the temperature for 3-4 hours.
[0012] Furthermore, in step S2, the process parameters of the high-energy ball milling are: the pre-synthesized powder is ball milled for 12-24 hours with alcohol or water as the medium, the rotation speed is 400-600r / min, and the high-energy ball milling is followed by drying.
[0013] Furthermore, after drying, the D50 particle size of the powder is 1.2-1.4 μm, and the D40 / D50 is 1.2-1.3.
[0014] Furthermore, the dried powder is mixed with a binder to form granules, and after passing through a 100-150 mesh sieve, the granules are cold pressed at a pressure of 100-200 MPa to obtain a ceramic body.
[0015] Furthermore, in step S2, sintering is carried out in an air environment by a powder embedding method at normal pressure, the temperature is increased to 500-600°C at a heating rate of no more than 5°C / min, and the temperature is kept for at least 1 hour to remove the binder, the temperature is increased to 1060-1140°C at a heating rate of no more than 6°C / min, and sintering is carried out for 3-4 hours. After sintering, the material is cooled in the furnace.
[0016] Furthermore, in step S3, the process parameters of the polarization are: heat preservation and pressure preservation for 20-30 minutes in high-temperature silicone oil at 120-150°C and a DC electric field of 12-14 kV / mm.
[0017] The beneficial effects brought by the technical solution provided by the embodiment of the present invention include:
[0018] 1. The ceramic composition of the present invention is a kind of ceramic composition having a high voltage coefficient d 33 and high Curie temperature T C The high-entropy calcium bismuth niobate-based high-temperature lead-free piezoelectric ceramics can be obtained using traditional piezoelectric ceramic preparation technology and industrial raw materials. The process is simple, the cost is low, the preparation is easy, there is no other second phase, the repeatability is good, and it is suitable for large-scale production.
[0019] 2. Compared with the conventional doped solid solution ceramic components, the present invention uses a high entropy strategy to significantly improve the piezoelectric activity of calcium bismuth niobate-based high-temperature lead-free piezoelectric ceramics, while maintaining its high T under the premise of improving its piezoelectricity. C Taking advantage of the advantages, a series of high-entropy bismuth calcium niobate-based high-temperature lead-free piezoelectric ceramics with excellent comprehensive piezoelectric properties were prepared. This method provides a new idea for the design and preparation of high-performance lead-free high-temperature piezoelectric ceramics. It is universal and can be applied to other bismuth layered structure oxide ceramic systems.
[0020] 3. Use high entropy strategy to reduce the content of Bi element and introduce sintering aids to reduce the sintering temperature and alleviate the volatilization of Bi element. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0022] Figure 1 XRD spectrum of the high-entropy calcium bismuth niobate-based high-temperature lead-free piezoelectric ceramic material prepared in an embodiment of the present invention;
[0023] Figure 2 Surface morphology of the high-entropy calcium bismuth niobate-based high-temperature lead-free piezoelectric ceramic material prepared in the embodiment of the present invention, a is CBN1; b is CBN2; c is CBN3; d is CBN4;
[0024] Figure 3 The dielectric temperature curve of CBN1 prepared in Example 1 of the present invention;
[0025] Figure 4 The dielectric temperature curve of CBN2 prepared in Example 2 of the present invention;
[0026] Figure 5 The dielectric temperature curve of CBN3 prepared in Example 3 of the present invention;
[0027] Figure 6 This is the dielectric temperature curve of CBN4 prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0029] The embodiment of the present invention discloses a high entropy calcium bismuth niobate-based high-temperature lead-free piezoelectric ceramic, characterized in that the chemical composition is Ca 1-x-y (Na 0.5 Bi 0.5 ) x Bi 2+y Ti y Nb 2-y-z Ta z O 9 +u wt%MO,0.1≤x≤0.9,0.1≤y≤0.9,0≤z≤5 / 3,0<u≤0.4, the MO is selected from B 2 O 3 , Fe 2 O 3 , CuO, MnO 2 One or more combinations of .
[0030] The present invention utilizes a high entropy strategy to 2 Nb 2 O 9 The perovskite layer in the system is adjusted, and the structure and performance are further regulated to obtain a component with excellent comprehensive piezoelectric properties to accelerate the practical application of lead-free ceramics in this system, and the composition is an orthorhombic ferroelectric phase with a high piezoelectric coefficient d 33 , high Curie temperature T C And high-temperature lead-free piezoelectric ceramics with excellent insulation performance; secondly, the high entropy strategy is used to reduce the content of Bi element and the introduction of sintering aids to reduce the sintering temperature can reduce the volatilization of Bi element. The high-temperature lead-free piezoelectric ceramics proposed in this application are used. 33 Greater than 20pC / N, Curie temperature greater than 900℃, and resistivity greater than 1×10 at 600℃ 6 Ω·cm, compared with the existing technology, the resistivity is improved by at least one order of magnitude.
[0031] Preferably, the chemical composition is: Ca 1 / 3 Na 1 / 6 Bi 5 / 2 Ti1 / 3 Nb 5 / 3-z Ta z O 9 +u wt%MO,0≤z≤5 / 3, the MO is selected from B 2 O 3 , Fe 2 O 3 , CuO, MnO 2 In this preferred technical solution, d 33 Greater than 20pC / N.
[0032] The embodiment of the present invention further provides a method for preparing the above-mentioned high-temperature lead-free piezoelectric ceramic, comprising the following steps:
[0033] S1. Weigh the raw materials of metal carbonate or oxide according to the stoichiometric ratio, mix and calcine once to obtain a pre-synthesized powder.
[0034] First, the raw materials of analytically pure or chemically pure carbonate or oxide are batched, and preferably dried after batching. The drying process in the embodiment of the present invention is to dry at least 10 hours under the condition of 200-250°C, which will not be described in detail below. After drying, mixing is performed, and the mixing is performed by ball milling. The mixing process is: the metal carbonate or oxide is ball milled for 8-12 hours with alcohol or water as the medium, and the speed is 300-500r / min, and then dried after the ball milling. Then a calcination is performed, and the process parameters of the calcination are: the mixed raw materials after drying are calcined in an air environment, the synthesis temperature is 800-900°C, and the heat preservation is 3-4h, and the pre-synthesized powder is obtained.
[0035] The present invention is directed to a compound having a chemical composition of Ca 1-x-y (Na 0.5 Bi 0.5 ) x Bi 2+y Ti y Nb 2-y-z Ta z O 9 The material of +u wt%MO is selected from carbonate or oxide raw materials. Preferably, the carbonate or metal oxide raw materials can be selected from calcium carbonate, anhydrous sodium carbonate, bismuth trioxide, titanium dioxide, niobium pentoxide, tantalum pentoxide, boron trioxide, iron trioxide, copper oxide, and manganese dioxide; the alcohol is preferably anhydrous ethanol.
[0036] S2. Add a sintering aid to the pre-synthesized powder according to a stoichiometric ratio, perform high-energy ball milling, mix and granulate, sieve, press and sinter to obtain a ceramic sample.
[0037] The process parameters of the high-energy ball milling are: the pre-synthesized powder and the sintering aid are ball milled for 12-24 hours with alcohol or water as the medium, the rotation speed is 400-600r / min, and the high-energy ball milling is followed by drying. Preferably, in the ball milling process, the material-to-ball ratio is 0.8-1.1, 400-450r / min ball milling is used for 4-5h, 500-600r / min ball milling is used for 8-19h, and after drying, the D50 particle size of the powder is 1.2-1.4μm, and D40 / D50 is 1.2-1.3; the particle size has a great influence on the performance of the product. Within the above particle size range, it can inhibit the burning loss of Bi during the sintering process, and facilitate the uniform mixing of the sintering aid and the pre-synthesized powder, thereby avoiding the uneven distribution of the sintering aid during the subsequent sintering process, resulting in poor local sintering, and the displacement of the Bi element during the sintering process due to the uneven distribution of the sintering aid. The dried powder is mixed with the binder to form The binder is added in an amount of 3wt% of the powder mass. In the embodiment of the present invention, the binder is PVB, which is passed through a 100-150 mesh sieve and then cold-pressed at a pressure of 100-200MPa to obtain a ceramic body. The ceramic body prepared in the embodiment of the present invention is a disc with a diameter of 8-10mm and a thickness of 1-1.4mm. The ceramic ligand is sintered in an air environment by a powder embedding method at normal pressure, and the temperature is increased to 500-600℃ at a heating rate of no more than 5℃ / min, and the temperature is kept for at least 1h to remove the binder, and the temperature is increased to 1060-1140℃ at a heating rate of no more than 6℃ / min, and the sintering is performed for 3-4h. After the sintering is completed, the ceramic sample is obtained by cooling with the furnace.
[0038] S3. The ceramic sample is polished, cleaned and dried, and then silver paste is applied to both end surfaces and polarized.
[0039] The polarization process parameters are: in high temperature silicone oil at 120-150° C., maintaining temperature and pressure for 20-30 minutes under a direct current electric field of 12-14 kV / mm.
[0040] In order to better illustrate the embodiments of the present invention, the present invention is further described in detail below through specific examples.
[0041] Example 1
[0042] The present invention provides a Ca 1 / 3 Na 1 / 6 Bi 5 / 2 Ti 1 / 3 Nb 5 / 3 O 9 High temperature lead-free piezoelectric ceramics and a preparation method thereof, comprising the following steps:
[0043] S1. Weigh the raw materials of metal carbonate or oxide according to the stoichiometric ratio, mix and calcine once to obtain a pre-synthesized powder. The metal carbonate or oxide is ball-milled for 8 hours with alcohol or water as the medium, the speed is 400r / min, and the ball milling is dried after the ball milling is completed; the process parameters of the first calcination are: the mixed raw materials after drying are calcined in an air environment, the synthesis temperature is 800℃, and the temperature is kept for 4 hours to obtain the pre-synthesized powder.
[0044] S2. Add a certain sintering aid to the pre-synthesized powder according to the stoichiometric ratio, perform high-energy ball milling, mix and granulate, press into tablets after screening, and sinter to obtain a ceramic sample. The process parameters of the high-energy ball milling are as follows: the pre-synthesized powder is ball milled for 12 hours with alcohol or water as the medium, the rotation speed is 400r / min, and the powder is dried after high-energy ball milling. After drying, it is mixed with a binder and granulated, and after passing through a 100-150 mesh sieve, it is cold-pressed at a pressure of 200MPa to obtain a ceramic body; the ceramic ligand is sintered in an air environment by a powder embedding method at normal pressure, and the temperature is increased to 500℃ at a heating rate of 3℃ / min and kept for 2h, and then increased to 1060℃ at a heating rate of 5℃ / min, sintered for 4h, and cooled with the furnace after sintering to obtain a ceramic sample.
[0045] S3. The ceramic sample is polished, cleaned and dried, and then silver paste is applied to both ends of the sample and polarized. The polarization process parameters are: in high-temperature silicone oil at 150°C, and in a DC electric field of 14kV / mm for 20 minutes. 1 / 3 Na 1 / 6 Bi 5 / 2 Ti 1 / 3 Nb 5 / 3 O 9 The piezoelectric ceramic is denoted as CBN1.
[0046] By calculating its mixing entropy ΔS mix is 1.78R, such as Figure 1 As shown, there is no impurity phase in CBN1, and the orthorhombic phase structure is dominant.
[0047] like Figure 2 As shown in a, the sample has a rod-like or sheet-like structure and is relatively dense; Figure 3 , Curie temperature T C is 906℃; through measurement, its d 33 The resistivity is 20.6pC / N and 1.6×10 6 Ω·cm.
[0048] Example 2
[0049] The present invention provides a Ca 1 / 3 Na 1 / 6 Bi5 / 2 Ti 1 / 3 Nb 5 / 3 O 9 High temperature lead-free piezoelectric ceramics and a preparation method thereof, comprising the following steps:
[0050] S1. Weigh the raw materials of metal carbonate or oxide according to the stoichiometric ratio, mix and calcine once to obtain a pre-synthesized powder. The metal carbonate or oxide is ball-milled for 8 hours with alcohol or water as the medium, the speed is 300r / min, and the ball milling is dried after the ball milling is completed; the process parameters of the first calcination are: the mixed raw materials after drying are calcined in an air environment, the synthesis temperature is 800℃, and the temperature is kept for 3 hours to obtain the pre-synthesized powder.
[0051] S2. Add a certain sintering aid to the pre-synthesized powder according to the stoichiometric ratio, perform high-energy ball milling, mix and granulate, press into tablets after screening, and sinter to obtain a ceramic sample. The process parameters of the high-energy ball milling are as follows: the pre-synthesized powder is ball milled for 12 hours with alcohol or water as the medium, the rotation speed is 400r / min, and the powder is dried after high-energy ball milling. After drying, it is mixed with a binder and granulated, and after passing through a 100-150 mesh sieve, it is cold-pressed at a pressure of 100MPa to obtain a ceramic body; the ceramic ligand is sintered in an air environment by a powder burying method at normal pressure, and the temperature is increased to 500℃ at a heating rate of 5℃ / min and kept for 1h, and then increased to 1060℃ at a heating rate of 6℃ / min, sintered for 3h, and cooled with the furnace after sintering to obtain a ceramic sample.
[0052] S3. The ceramic sample is polished, cleaned and dried, and then silver paste is applied to both ends of the sample and polarized. The polarization process parameters are: in high temperature silicone oil at 120°C, and in a DC electric field of 12kV / mm for 20 minutes. 1 / 3 Na 1 / 6 Bi 5 / 2 Ti 1 / 3 Nb 5 / 3 O 9 The piezoelectric ceramic is denoted as CBN11.
[0053] By calculating its mixing entropy ΔS mix The Curie temperature T is 1.78R, and there is no impurity phase in CBN11, which is mainly orthorhombic phase structure. The sample has a rod-like or sheet-like structure, which is relatively dense. C At 905℃, through measurement, its d 33 The resistivity is 20.2pC / N and 1.5×10 6 Ω·cm.
[0054] Example 3
[0055] The present invention provides a Ca1 / 3 Na 1 / 6 Bi 5 / 2 Ti 1 / 3 Nb 5 / 3 O 9 High temperature lead-free piezoelectric ceramics and a preparation method thereof, comprising the following steps:
[0056] S1. Weigh the raw materials of metal carbonate or oxide according to the stoichiometric ratio, mix and calcine once to obtain a pre-synthesized powder. The metal carbonate or oxide is ball-milled for 12 hours with alcohol or water as the medium, and the speed is 500r / min. After the ball milling, it is dried; the process parameters of the first calcination are: calcine the dried mixed raw materials in an air environment, the synthesis temperature is 900℃, and the temperature is kept for 4 hours to obtain the pre-synthesized powder.
[0057] S2. Add a certain sintering aid to the pre-synthesized powder according to the stoichiometric ratio, perform high-energy ball milling, mix and granulate, press into tablets after screening, and sinter to obtain a ceramic sample. The process parameters of the high-energy ball milling are as follows: the pre-synthesized powder is ball milled for 24 hours with alcohol or water as the medium, the rotation speed is 600r / min, and the powder is dried after high-energy ball milling. After drying, it is mixed with a binder and granulated, and after passing through a 100-150 mesh sieve, it is cold-pressed at a pressure of 200MPa to obtain a ceramic body; the ceramic ligand is sintered in an air environment by a powder embedding method at normal pressure, and the temperature is increased to 600℃ at a heating rate of 3℃ / min and kept for 2h, and then increased to 1140℃ at a heating rate of 5℃ / min, sintered for 4h, and cooled with the furnace after sintering to obtain a ceramic sample.
[0058] S3. After polishing, cleaning and drying the ceramic sample, silver paste is applied to both ends of the sample and polarization is performed. The polarization process parameters are: in high-temperature silicone oil at 150°C, and in a DC electric field of 14kV / mm for 30 minutes. 1 / 3 Na 1 / 6 Bi 5 / 2 Ti 1 / 3 Nb 5 / 3 O 9 The piezoelectric ceramic is denoted as CBN12.
[0059] By calculating its mixing entropy ΔS mix The Curie temperature T is 1.78R, and there is no impurity phase in CBN12, which is mainly orthorhombic phase structure. The sample has a rod-like or sheet-like structure, which is relatively dense. C is 907℃, through measurement, its d 33 The resistivity is 21.2pC / N and 2.3×10 6 Ω·cm.
[0060] Example 4
[0061] Different from Example 1, in step S2 of this example, in the ball milling process, the material-to-ball ratio is 0.8, ball milling is performed at 400 r / min for 4 h and 500 r / min for 8 h, and after drying, the D50 particle size of the powder is 1.4 μm, and D40 / D50 is 1.2. The prepared piezoelectric ceramic is denoted as CBN13.
[0062] By calculating its mixing entropy ΔS mix The Curie temperature T is 1.78R, and there is no impurity phase in CBN13, which is mainly orthorhombic phase structure. The sample has a rod-like or sheet-like structure, which is relatively dense. C At 910℃, through measurement, its d 33 The resistivity is 23.2pC / N and 4.3×10 6 Ω·cm.
[0063] Example 5
[0064] Different from Example 1, in step S2 of this example, in the ball milling process, the material-to-ball ratio is 1.1, 450 r / min ball milling is used for 5 h, 600 r / min ball milling is used for 19 h, and after drying, the D50 particle size of the powder is 1.2 μm, and D40 / D50 is 1.3. The prepared piezoelectric ceramic is recorded as CBN14.
[0065] By calculating its mixing entropy ΔS mix The Curie temperature T is 1.78R, and there is no impurity phase in CBN14, which is mainly orthorhombic phase structure. The sample has a rod-like or flake-like structure, which is relatively dense. C At 910℃, through measurement, its d 33 The resistivity is 24.6pC / N and 3.9×10 6 Ω·cm.
[0066] Example 6
[0067] The embodiment of the present invention provides Ca 1 / 3 Na 1 / 6 Bi 5 / 2 Ti 1 / 3 Nb 2 / 3 O 9 The preparation method comprises the following steps:
[0068] S1. Weigh the raw materials of metal carbonate or oxide according to the stoichiometric ratio, mix and calcine once to obtain a pre-synthesized powder. The metal carbonate or oxide is ball-milled for 8 hours with alcohol or water as the medium, the speed is 300r / min, and the ball milling is dried after the ball milling is completed; the process parameters of the first calcination are: calcine the dried mixed raw materials in an air environment, the synthesis temperature is 850℃, and the temperature is kept for 3 hours to obtain the pre-synthesized powder.
[0069] S2. Add a certain sintering aid to the pre-synthesized powder according to the stoichiometric ratio, perform high-energy ball milling, mix and granulate, press into tablets after screening, and sinter to obtain a ceramic sample. The process parameters of the high-energy ball milling are as follows: the pre-synthesized powder is ball milled for 8 hours with alcohol or water as the medium, the rotation speed is 300r / min, and the powder is dried after high-energy ball milling. After drying, it is mixed with a binder and granulated, and after passing through a 100-150 mesh sieve, it is cold-pressed at a pressure of 200MPa to obtain a ceramic body; the ceramic ligand is sintered in an air environment by a powder embedding method at normal pressure, and the temperature is increased to 550℃ at a heating rate of 3℃ / min and kept for 1h, and then increased to 1100℃ at a heating rate of 5℃ / min, sintered for 3h, and cooled with the furnace after sintering to obtain a ceramic sample.
[0070] S3. The ceramic sample is polished, cleaned and dried, and then silver paste is applied to both ends of the sample and polarized. The polarization process parameters are: in high-temperature silicone oil at 150°C, and in a DC electric field of 14kV / mm for 20 minutes. 1 / 3 Na 1 / 6 Bi 5 / 2 Ti 1 / 3 Nb 2 / 3 O 9 The piezoelectric ceramic is denoted as CBN2.
[0071] By calculating its mixing entropy ΔS mix is 2.34R (high entropy); Figure 1 As shown, the piezoelectric ceramic prepared in this embodiment does not have any impurity phase and is mainly in an orthorhombic phase structure.
[0072] like Figure 2 As shown in b, the sample has a rod-like or sheet-like structure and is relatively dense; Figure 4 , Curie temperature T C is 901℃. After measurement, its d 33 The resistivity is 22.7pC / N and 1.2×10 7 Ω·cm.
[0073] Example 7
[0074] The embodiment of the present invention provides Ca 1 / 3 Na 1 / 6 Bi 5 / 2 Ti 1 / 3 Nb 1 / 3 Ta 4 / 3 O 9 The preparation method comprises the following steps:
[0075] S1. Weigh the raw materials of metal carbonate or oxide according to the stoichiometric ratio, mix and calcine once to obtain a pre-synthesized powder. The metal carbonate or oxide is ball-milled for 8 hours with alcohol or water as the medium, the speed is 300r / min, and the ball milling is dried after the ball milling is completed; the process parameters of the first calcination are: calcine the mixed raw materials after drying in an air environment, the synthesis temperature is 900℃, and the temperature is kept for 3 hours to obtain the pre-synthesized powder.
[0076] S2. Add a certain sintering aid to the pre-synthesized powder according to the stoichiometric ratio, perform high-energy ball milling, mix and granulate, press the tablets after screening, and sinter to obtain a ceramic sample. The process parameters of the high-energy ball milling are as follows: the pre-synthesized powder is ball milled for 12 hours with alcohol or water as the medium, the rotation speed is 500r / min, and the powder is dried after high-energy ball milling. After drying, the D50 particle size of the powder is 1.4μm, and D40 / D50 is 1.2; the dried powder is mixed with a binder and granulated, and after passing through a 100-150 mesh sieve, it is cold pressed under a pressure of 100MPa to obtain a ceramic body; the ceramic ligand is sintered in an air environment by a powder burying method at normal pressure, and the temperature is increased to 550℃ at a heating rate of 3℃ / min and kept for 2h, and then increased to 1120℃ at a heating rate of 4℃ / min, sintered for 4h, and cooled with the furnace after sintering to obtain a ceramic sample.
[0077] S3. The ceramic sample is polished, cleaned and dried, and then silver paste is applied to both ends of the sample and polarized. The polarization process parameters are: in high temperature silicone oil at 180°C, and in a DC electric field of 12kV / mm for 20 minutes. 1 / 3 Na 1 / 6 Bi 5 / 2 Ti 1 / Nb 1 / 3 Ta 4 / 3 O 9 The piezoelectric ceramic is denoted as CBN3.
[0078] By calculating its mixing entropy ΔS mix is 2.20R; Figure 1 The prepared piezoelectric ceramic CBN3 does not contain any impurity phase and is mainly composed of an orthorhombic phase structure.
[0079] like Figure 2 As shown in c, the sample has a rod-like or sheet-like structure and is relatively dense; Figure 5 , Curie temperature T C is 903℃. After measurement, its d 33 The resistivity is 31.5pC / N and 1.6×10 7 Ω·cm.
[0080] Example 8
[0081] The embodiment of the present invention provides Ca 1 / 3 Na 1 / 6 Bi 5 / 2 Ti 1 / 3 Ta 5 / 3 O 9 The preparation method comprises the following steps:
[0082] S1. Weigh the raw materials of metal carbonate or oxide according to the stoichiometric ratio, mix and calcine once to obtain a pre-synthesized powder. The metal carbonate or oxide is ball-milled for 8 hours with alcohol or water as the medium, the speed is 300r / min, and the ball milling is dried after the ball milling is completed; the process parameters of the first calcination are: the mixed raw materials after drying are calcined in an air environment, the synthesis temperature is 900°C, and the temperature is kept for 4 hours to obtain the pre-synthesized powder.
[0083] S2. Add a certain sintering aid to the pre-synthesized powder according to the stoichiometric ratio, perform high-energy ball milling, mix and granulate, press the tablets after screening, and sinter to obtain a ceramic sample. The process parameters of the high-energy ball milling are as follows: the pre-synthesized powder is ball milled for 12 hours with alcohol or water as the medium, the rotation speed is 500r / min, and the powder is dried after high-energy ball milling. After drying, the D50 particle size of the powder is 1.4μm, and D40 / D50 is 1.2; the dried powder is mixed with a binder and granulated, and after passing through a 100-150 mesh sieve, it is cold pressed under a pressure of 100MPa to obtain a ceramic body; the ceramic ligand is sintered in an air environment by a powder burying method at normal pressure, and the temperature is increased to 600℃ at a heating rate of 4℃ / min and kept for 2h, and then increased to 1140℃ at a heating rate of 4℃ / min, sintered for 4h, and cooled with the furnace after sintering to obtain a ceramic sample.
[0084] S3. The ceramic sample is polished, cleaned and dried, and then silver paste is applied to both ends of the sample and polarized. The polarization process parameters are: in high-temperature silicone oil at 180°C, and in a DC electric field of 13kV / mm for 20 minutes. 1 / 3 Na 1 / 6 Bi 5 / 2 Ti 1 / 3 Ta 5 / 3 O 9 The piezoelectric ceramic is denoted as CBN4.
[0085] By calculating its mixing entropy ΔS mix is 1.78R; Figure 1 The prepared piezoelectric ceramic CBN4 does not contain any impurities and is mainly composed of an orthorhombic phase structure. Figure 2 As shown in d, the sample has a rod-like or sheet-like structure and is relatively dense; Figure 6 , Curie temperature T Cis 908℃. After measurement, its d 33 The resistivity is 26.5pC / N and 4.0×10 6 Ω·cm.
[0086] Comparative Example 1
[0087] Different from Example 1, this comparative example prepares CaBi 2 Nb 2 O 9 Piezoelectric ceramics.
[0088] Its mixing entropy ΔS mix 0; CBN0 does not have any impurity phase and is mainly composed of an orthorhombic phase structure.
[0089] After measurement, its d 33 The resistivity is 5.8pC / N and 4.3×10 5 Ω·cm.
[0090] Comparative Example 2
[0091] Different from Example 1, the powder prepared in this comparative example has a particle size D50 of 2.6 μm and a D40 / D50 of 1.2.
[0092] By calculating its mixing entropy ΔS mix is 1.78R; there is no impurity phase, and the orthorhombic phase structure is the main one. After measurement, its d 33 The resistivity is 17.4pC / N and 1.2×10 6 Ω·cm.
[0093] By comparing the embodiment with comparative example 1, it can be seen that the phase structure remains unchanged when the high entropy strategy is introduced. 33 Significantly improved, maintain high T C By comparing Examples 1, 4, 5 and Comparative Example 2, it can be seen that when the D50 particle size of the powder is 1.2-1.4 μm and D40 / D50 is 1.2-1.3, d 33 Significant improvement.
[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A high entropy calcium bismuth niobate-based high temperature lead-free piezoelectric ceramic, characterized in that: The chemical composition is Ca 1-x-y (Na 0.5 Bi 0.5 ) x Bi 2+y Ti y Nb 2-y-z Ta z O9+u wt%MO, 0.1≤x≤0.9, 0.1≤y≤0.9, 0≤z≤5 / 3, 0<u≤0.4, wherein MO is selected from one or more combinations of B2O3, Fe2O3, CuO and MnO2.
2. The high entropy calcium bismuth niobate-based high temperature lead-free piezoelectric ceramic according to claim 1, characterized in that: Chemical composition: Ca 1 / 3 Na 1 / 6 Bi 5 / 2 Ti 1 / 3 Nb 5 / 3-z Ta z O9+u wt%MO,0≤z≤5 / 3, wherein MO is selected from one or more combinations of B2O3, Fe2O3, CuO, and MnO2.
3. A method for preparing the high-entropy calcium bismuth niobate-based high-temperature lead-free piezoelectric ceramic according to claim 1 or 2, characterized in that: The following steps are involved: S1. Weighing the raw materials of metal carbonate or oxide according to the stoichiometric ratio, mixing and calcining once to obtain a pre-synthesized powder; S2. The pre-synthesized powder is added with a sintering aid in a stoichiometric ratio, subjected to high-energy ball milling, mixed and granulated, sieved, pressed and sintered to obtain a ceramic sample; S3. The ceramic sample is polished, cleaned and dried, and then silver paste is applied to both end surfaces and polarized.
4. The method for preparing high-entropy calcium bismuth niobate-based high-temperature lead-free piezoelectric ceramic according to claim 3, characterized in that: In the step S1, the mixing is as follows: the metal carbonate or oxide is ball-milled for 8-12 hours with alcohol or water as the medium at a rotation speed of 300-500 r / min, and then dried after the ball-milling.
5. The method for preparing high-entropy calcium bismuth niobate-based high-temperature lead-free piezoelectric ceramics according to claim 3, characterized in that: The process parameters of the primary calcination are: calcining the dried mixed raw materials in an air environment, with a synthesis temperature of 800-900° C. and keeping the temperature for 3-4 hours.
6. The method for preparing high-entropy calcium bismuth niobate-based high-temperature lead-free piezoelectric ceramic according to claim 3, characterized in that: In the step S2, the process parameters of the high-energy ball milling are: the pre-synthesized powder is ball milled for 12-24 hours with alcohol or water as the medium, the rotation speed is 400-600r / min, and the powder is dried after the high-energy ball milling.
7. The method for preparing high-entropy calcium bismuth niobate-based high-temperature lead-free piezoelectric ceramics according to claim 6, characterized in that: After drying, the D50 particle size of the powder is 1.2-1.4 μm, and the D40 / D50 is 1.2-1.
3.
8. The method for preparing high-entropy calcium bismuth niobate-based high-temperature lead-free piezoelectric ceramics according to claim 6, characterized in that: The dried powder is mixed with a binder to form granules, passed through a 100-150 mesh sieve, and then cold pressed at a pressure of 100-200 MPa to obtain a ceramic body.
9. The method for preparing high-entropy calcium bismuth niobate-based high-temperature lead-free piezoelectric ceramics according to claim 3, characterized in that: In the step S2, sintering is carried out in an air environment by using a powder embedding method at normal pressure, heating to 500-600°C at a heating rate of no more than 5°C / min, keeping the temperature for at least 1 hour to remove the binder, heating to 1060-1140°C at a heating rate of no more than 6°C / min, sintering for 3-4 hours, and cooling with the furnace after sintering.
10. The method for preparing high-entropy calcium bismuth niobate-based high-temperature lead-free piezoelectric ceramics according to claim 3, characterized in that: In step S3, the process parameters of the polarization are: in high-temperature silicone oil at 120-150° C., the temperature and pressure are maintained for 20-30 minutes under a DC electric field of 12-14 kV / mm.
Citation Information
Patent Citations
Method for enhancing performance of calcium bismuth niobate high-temperature piezoelectric ceramic through oxide sintering aid induced texture
CN114560698A
High-entropy calcium bismuth niobate-based lead-free piezoelectric ceramic material and preparation method thereof
CN117586008A
Bismuth calcium niobate-based bismuth layered structure ferroelectric piezoelectric ceramic and preparation method thereof
CN117964359A
Piezoelectric ceramics
JP2000264733A
Piezoelectric ceramic, and piezoelectric, dielectric, and pyroelectric elements using the piezoelectric ceramic
WO2008143160A1